IMPROVING EMPLOYEE’S PRODUCTIVITY USING WORK-LIFE BALANCE ANALYSIS IN PROJECT BASED CONSTRUCTION COMPANY - Gunawan Handoko; Henndy Ginting (Sean Institute, 2023)
The world of construction is a world full of limitations, from limited time to complete a project to limited human resources to complete the project. Therefore, balance is needed to maintain physical and mental health stability. One way to maintain mental health is to maintain a work-life balance. PT Total Bangun Persada, Tbk is a construction company that focusesfocusingand customers. To achieve this, a fairly high productivity rate is needed. This study aims to help companies increase productivity by using work-life balance analysis, which has three indicators: time balance, involvement balance, and satisfaction balance. This study recommends implementing policies in projects with the aim of increasing the level of work-life balance, which will impact employee productivity.